REPRESENTASI PEREMPUAN ERA ORDE BARU DALAM MUSIK ANAK POPULAR INDONESIA KARYA PAPA T. BOB - Suci Amalia; Lily Tjahjandari (Metahumaniora, 2023)
According to studies on popular children’s songs, songs can be a medium for forming a child’s mindset through reflection and memories contained in the lyrics and video clips of the songs. Popular children’s songs can also be used to spread gender ideology. Using Simone de Beauvoir’s gender approach and Julia Suryakusuma’s Ibuism Negara (National Motherism), this research demonstrates elements of gender inequality found in two songs by Papa T. Bob, namely Dudidudidam (video clip: Enno Lerian) and Papa Cinta Mama (video clip: Saskia and Savira), both created during the reign of the New Order. These elements combine to form the concept of family, which was developed during the New Order government. The results of this study’s analysis, using a descriptive qualitative approach and a read-see technique, lead to the domestication and objectification of women in the New Order era family concept attached to children in the lyrics and videos of popular children’s songs entitled Dudidudidam and Papa Cinta by Papa T. Bob.